Physiotherapeutic conduct in amyotrophic lateral sclerosis - Pozza, Andreza Martinez; Delamura, Milene Karenine; Ramirez, Clarissa; Valério, Nelson Iguimar; Marino, Laís Helena Carvalho; Lamari, Neuseli Marino (São Paulo Medical Journal, 2006)
Amyotrophic Lateral Sclerosis (ALS) is a fatal progressive neurodegenerative disease with multifactorial etiology for which, so far, there is no effective medicinal treatment. However, by means of kinesiotherapy intervention and patient guidance and care, physiotherapy can delay physical functional losses, muscle fatigue and immobility of the joint muscle system, thereby improving the quality of life. This survey had the aim of reviewing the physiotherapeutic conduct currently used in ALS cases. Monthly monitoring is recommended, with changes in goals and conduct at each stage of the disease, activities to be pursued around the home, and emphasis on stretching, muscle strengthening, posture adequacy and respiratory kinesiotherapy.